MODELING THE CONTROL PANEL CIRCUIT FOR NICE 3000 ELEVATOR 5 FLOORS USING ELECTRICAL CONTROL TECHNIQUES SIMULATOR SOFTWARE - Mohammad Zidan Alfariki; Rizky Mubarok (Program Studi Teknik Elektro Universitas Peradaban, 2022)
Elevator or is one of the tools that serves to facilitate human activities whose routines are more often in a storied room. The existence of this elevator is a substitute for the function of the stairs in reaching each subsequent floor in a multi-storey building. This study simulates a 5-floor elevator control circuit using electrical control techniques simulator software. The use of this application is very helpful for simulating control circuits before the equipment is installed and assembled. Useful for minimizing failures and troubleshooting of the circuit. Based on the results and discussion of the research, there are three main circuits in the control circuit, the new contact circuit and the power circuit. The connection of the power circuit to the motor between the UP contactor and DOWN contactor is not the same. UP contactor connection and motor (R and U), ( V and T ), (T and W). While DOWN contactor and motor (T and U), (V and R), (R and W). This circuit is commonly called an interlock circuit in which the two auxiliary contacts are locked between the auxiliary contact (R. NC) and the auxiliary contact (F.NC) which ensures that they cannot work simultaneously. The process of the elevator going up (UP) has been successful and shows a simulation of the lit going up and without any errors. And the elevator down (DOWN) process has been successful and shows the simulation of the lit going up and up without any errors